Clopidogrel use After Myocardial Revascularization: Prevalence, Predictors, and One-Year Survival Rate - Prates,Paulo Roberto L. (2016)
Abstract Introduction: Antiplatelet therapy after coronary artery bypass graft (CABG) has been used. Little is known about the predictors and efficacy of clopidogrel in this scenario. Objective: Identify predictors of clopidogrel following CABG. Methods: We evaluated 5404 patients who underwent CABG between 2000 and 2009 at Duke University Medical Center. We excluded patients undergoing concomitant valve surgery, those who had postoperative bleeding or death before discharge. Postoperative clopidogrel was left to the discretion of the attending physician. Adjusted risk for 1-year mortality was compared between patients receiving and not receiving clopidogrel during hospitalization after undergoing CABG. Results: At hospital discharge, 931 (17.2%) patients were receiving clopidogrel. Comparing patients not receiving clopidogrel at discharge, users had more comorbidities, including hyperlipidemia, hypertension, heart failure, peripheral arterial disease and cerebrovascular disease. Patients who received aspirin during hospitalization were less likely to receive clopidogrel at discharge (P≤0.0001). Clopidogrel was associated with similar 1-year mortality compared with those who did not use clopidogrel (4.4% vs. 4.5%, P=0.72). There was, however, an interaction between the use of cardiopulmonary bypass and clopidogrel, with lower 1-year mortality in patients undergoing off-pump CABG who received clopidogrel, but not those undergoing conventional CABG (2.6% vs 5.6%, P Interaction = 0.032). Conclusion: Clopidogrel was used in nearly one-fifth of patients after CABG. Its use was not associated with lower mortality after 1 year in general, but lower mortality rate in those undergoing off-pump CABG. Randomized clinical trials are needed to determine the benefit of routine use of clopidogrel in CABG.